2018
DOI: 10.1017/s1759078718001150
|View full text |Cite
|
Sign up to set email alerts
|

Frequency reconfigurable antenna for cognitive radios with sequential UWB mode of perception and multiband mode of operation

Abstract: In this work, an UWB/narrow band reconfigurable elliptical-shaped monopole antenna for cognitive radio applications with sequential perception and operation modes is presented. The proposed approach consists in integrating a reconfigurable filter, in an UWB antenna ground plan, by the mean of four horizontal slots and integrated switches that allow inserting/removing/varying zeros and poles in the frequency response. By acting on the slot lengths in order to alter their resonance frequencies, the different swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to ( [17]- [19]) it can be observed that the Frequency reconfigurable antenna has been extensively employed in wireless communication system applications, especially in Cognitive Radio (CR). Nonetheless, microstrip patch antenna has been reported in the previous literature to suffer from design and biasing complexity, large size of antenna and switching techniques implementation [20]. This paper achieved small size comparing with study of ( [20]- [22] ), where the dimentions were (L = 84 mm, W= 84 mm, L = 70 mm, W= 100 mm and 66mm X 90 mm x 1.3mm respectively.…”
Section: Simulation Results and Discussionmentioning
confidence: 86%
“…According to ( [17]- [19]) it can be observed that the Frequency reconfigurable antenna has been extensively employed in wireless communication system applications, especially in Cognitive Radio (CR). Nonetheless, microstrip patch antenna has been reported in the previous literature to suffer from design and biasing complexity, large size of antenna and switching techniques implementation [20]. This paper achieved small size comparing with study of ( [20]- [22] ), where the dimentions were (L = 84 mm, W= 84 mm, L = 70 mm, W= 100 mm and 66mm X 90 mm x 1.3mm respectively.…”
Section: Simulation Results and Discussionmentioning
confidence: 86%